Pengaruh Interaksi Host dan Diskon Flash Sale Terhadap Ketertarikan Konsumen dalam Live Shopping di Shopee pada Masyarakat di Kota Surabaya - Yusran Syaroni; Iswati Iswati; Siti Aisah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to examine the influence of host interaction and flash sale discounts on consumer interest in live shopping on Shopee among the community in Surabaya City. The research employs a quantitative approach using a structured questionnaire as the primary data collection method. A total of 96 respondents, all of whom actively engage in online shopping via Shopee, were selected as the study sample. Data analysis was conducted using SPSS, applying both t-tests and F-tests to evaluate the hypotheses. The t-test results reveal that host interaction significantly affects consumer interest, with a t-count value of 5.252 exceeding the t-table value of 1.986, and a significance level of 0.000, which is below the 0.05 threshold. Similarly, flash sale discounts also demonstrate a significant effect on consumer interest, with a t-count value of 3.217 surpassing the t-table value of 1.986, and a significance level of 0.002, indicating statistical significance. Furthermore, the F-test results indicate that host interaction and flash sale discounts have a simultaneous and significant influence on consumer interest, as evidenced by an F-count value of 26.37 exceeding the F-table value of 3.9434, with a significance level of 0.000. These findings suggest that both host interaction and flash sale discounts play a crucial role in shaping consumer purchasing interest during live shopping events. The results highlight the importance for resellers and online sellers to enhance host engagement skills and strategically implement time-limited discount offers to attract and retain consumers. In the increasingly competitive e-commerce environment, optimizing these two factors may significantly contribute to improving customer engagement and driving sales performance. This research provides practical insights for online retailers seeking to strengthen their marketing strategies on live shopping platforms